พลวัตและเสถียรภาพของความยืดหยุ่นของอุปสงค์การท่องเที่ยวไทยในระยะยาวในตลาดนักท่องเที่ยวชาวจีน: The Dynamics and Stability of the Elasticities of Demand for Thailand’s Long-run Tourism for Chinese Tourists’ Market - อั้นทอง, อัครพงศ์ (Journal of Applied Economics and Management Strategy, 2016)
บทความนี้วิเคราะห์การเปลี่ยนแปลงและตรวจสอบเสถียรภาพความยืดหยุ่นของอุปสงค์การท่องเที่ยวไทยในระยะยาวในตลาดนักท่องเที่ยวชาวจีน โดยประยุกต์ใช้Long-run static model of time varying parameter (TVP-LRM) พิจารณาพลวัตความยืดหยุ่น และใช้ค่าสัมประสิทธิ์ความแปรปรวน (Coefficient of Variation: COV) ร่วมกับดัชนีความไม่มีเสถียรภาพ (Instability Index: I) พิจารณาเสถียรภาพความยืดหยุ่นผลการศึกษา พบว่า การขยายตัวของเศรษฐกิจจีนมีส่วนช่วยกระตุ้นให้เกิดการเติบโตของตลาดนักท่องเที่ยวชาวจีนในไทย และตลาดนักท่องเที่ยวชาวจีนตอบสนองต่อราคาการท่องเที่ยวไทยมากกว่าราคาของคู่แข่งโดยความยืดหยุ่นของอุปสงค์การท่องเที่ยวไทยในระยะยาวมีการเปลี่ยนแปลงตามเวลาแต่มีเสถียรภาพมากขึ้นหลังปี พ.ศ. 2555 ความยืดหยุ่นต่อรายได้มีแนวโน้มดีขึ้น และการท่องเที่ยวไทยมีความได้เปรียบในการแข่งขันด้านราคาเพิ่มขึ้นเช่นเดียวกัน ความยืดหยุ่นต่อรายได้ยังคงมีเสถียรภาพมากที่สุด รองลงมาได้แก่ความยืดหยุ่นไขว้ส่วนความยืดหยุ่นต่อราคามีเสถียรภาพน้อยที่สุด อย่างไรก็ตาม หลังปี พ.ศ. 2552 ความยืดหยุ่นของอุปสงค์การท่องเที่ยวไทยไม่มีบทบาทในการรักษาเสถียรภาพการขยายตัวของจำนวนนักท่องเที่ยวชาวจีน ผลการศึกษาแสดงให้เห็นว่า ตลาดนักท่องเที่ยวชาวจีนยังคงเติบโตอย่างต่อเนื่องตามการขยายตัวของเศรษฐกิจจีน ดังนั้นไทยควรให้ความสำคัญกับการเตรียมความพร้อมเพื่อรองรับการขยายตัวของตลาดนักท่องเที่ยวชาวจีนในอนาคตและไม่ควรใช้นโยบายราคาในการแข่งขันและ/รักษาเสถียรภาพการขยายตัวของจำนวนนักท่องเที่ยวชาวจีน This article analyzes the change and examines the stability of Thailand’s long-run tourism demand elasticities in Chinese tourists’ market. Long-run static model of time varying parameter (TVP-LRM) is used to consider the dynamics of elasticities, and we applied the coefficient of variation (COV) and instability index (I) to examine the stability of elasticities. The results show that economic growth of China helped to stimulate the expansion of Chinese tourists’ market in Thailand and Chinese tourists respond to a change in Thailand’s price less than the changes in the competitors’ prices. The study finds that Thailand’s long-run tourism demand elasticities have changed over time, but showed greater stability. After 2012, the income elasticity has increased and price-competitive advantage of Thailand’s tourism has improved as well. Income elasticity shows the most stability, follows by cross-price and price elasticity, respectively. However, after 2009 the stability of Thailand’s tourism demand elasticities have not played a stabilizing role in the growth of Chinese's tourists. The study shows that Chinese’s tourists’ market continues to growth steadily in line with the expansion of Chinese’s economy. Therefore, Thailand should focus on increasing capacity for this market and do not use the price competition and maintain stabilized expansion of Chinese’s tourists’ market.